Identity-based security solutions for mobile ad hoc networks - Bohio, Muhammad Junaid (University of Ottawa (Canada), 2004)
In this thesis, we propose security solutions for pairwise and broadcast communication in mobile ad hoc networks. We use identity-based keys that do not require certificates and that simplify key management. We use pairwise symmetric keys that are computed non-interactively by the nodes, which reduces communication overhead. Our pairwise-key management protocol requires a minimum number of keys, O(N), to be generated by the third party as compared to the conventional pairwise schemes with O(N2). We also propose an efficient identity-based signature scheme for an authenticated broadcast protocol, a collision-free method for computing broadcast keys, a key escrow free scheme and a signcryption scheme as an alternative to our signature-encryption algorithm for broadcast protocol. Since in the group key distribution in mobile ad hoc networks there is the possibility of packet loss due to the mobility of users and wireless channels, we also propose self-healing, mutual-healing and some optimization techniques for the recovery of lost session keys.
Keywords: Engineering, Electronics and Electrical.